1994
DOI: 10.2172/10184645
|View full text |Cite
|
Sign up to set email alerts
|

Reentry safety for the Topaz II Space Reactor: Issues and analyses

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Analysis from both safety and safeguard perspectives concluded that cold reentry accidents posed negligible radiological and only minor safeguards risk "regardless of whether the core impacts the earth and remains intact or if all or part of the core disassembles during reentry or upon impact." 25 Therefore, the safety team opted not to place a functional safety requirement for cold reentry. A partial burnup and dispersal of HEU would have to be reexamined and as it may not be considered acceptable in today's nuclear security environment.…”
Section: Russian Bukmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis from both safety and safeguard perspectives concluded that cold reentry accidents posed negligible radiological and only minor safeguards risk "regardless of whether the core impacts the earth and remains intact or if all or part of the core disassembles during reentry or upon impact." 25 Therefore, the safety team opted not to place a functional safety requirement for cold reentry. A partial burnup and dispersal of HEU would have to be reexamined and as it may not be considered acceptable in today's nuclear security environment.…”
Section: Russian Bukmentioning
confidence: 99%
“…The SP-100 and the US/Russian Topaz II space power programs evaluated the security risks during launch and provided guidelines to minimize the potential risk under accident conditions. [24][25][26] In both programs, the use of HEU was not an issue.…”
mentioning
confidence: 99%